2007
DOI: 10.1063/1.2753681
|View full text |Cite
|
Sign up to set email alerts
|

The effects of annealing on the structural, optical, and vibrational properties of lattice-matched GaAsSbN∕GaAs grown by molecular beam epitaxy

Abstract: The structural, optical, and vibrational properties of a GaAsSbN epilayer lattice matched to GaAs with a band gap of 1eV have been investigated using a variety of characterization techniques. These layers have potential applications in GaAs based tandem solar cells that utilize the near infrared region of the solar spectrum. The epilayers were grown in an elemental solid source molecular beam epitaxy system with a rf plasma nitrogen source. The Sb and N compositions of the nearly lattice-matched layers are 6.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
5
14
0
Order By: Relevance
“…Comparing the different samples, it can be noticed that the annealing process under As overpressure (insitu annealed sample) presents a higher redshift, getting closer to our 1 eV bandgap target, the lowest FWHM as well as the smallest energy bandgap shift along the growth direction. Our results are coherent with previous studies, where it was reported that the PL characteristics of the in-situ annealed samples (As atmosphere) were better than those of the ex-situ annealed samples [7,9,10]. The reason argued for this improvement was a more efficient elimination of N-related recombination centers [9,10], as well as a suppression of both N and As out-diffusion that leads to an improvement of Ga-N bonding [7].…”
Section: Additionally Insupporting
confidence: 91%
See 3 more Smart Citations
“…Comparing the different samples, it can be noticed that the annealing process under As overpressure (insitu annealed sample) presents a higher redshift, getting closer to our 1 eV bandgap target, the lowest FWHM as well as the smallest energy bandgap shift along the growth direction. Our results are coherent with previous studies, where it was reported that the PL characteristics of the in-situ annealed samples (As atmosphere) were better than those of the ex-situ annealed samples [7,9,10]. The reason argued for this improvement was a more efficient elimination of N-related recombination centers [9,10], as well as a suppression of both N and As out-diffusion that leads to an improvement of Ga-N bonding [7].…”
Section: Additionally Insupporting
confidence: 91%
“…The final authenticated version is available online at: https://doi.org/10.1007/s11664-018-6325-3 5 increment in the N content in the GaNSbAs layer due to the annealing process in N ambient [7], which would cause an As desorption and a N incorporation at such high temperature. Both hypotheses are coherent with the fact that the intensity of this low energy band increases closer to the surface.…”
Section: Additionally Inmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 3.9, the variation in FWHM with temperature is less and T deloc is smaller in sample N2 due to the smaller range of values of the localization energies. In sample N1, the FWHM exhibits a small inverted S-curve, that is, a mild dip in the FWHM curve as the temperature approaches T deloc , which is a signature of strong exciton localization normally observed in dilute nitride system [39][40][41]. The T deloc is considerably larger for this sample.…”
Section: Photoluminescencementioning
confidence: 92%